(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article discusses the work being carried out in the Republic of Uzbekistan on the transition of financial statements to international standards and the results achieved. It also discusses the advantages of transitioning financial statements to international standards.